FOMENTO ÀS OBRAS MUNICIPAIS: O PROJETO "REPRESENTANTE CAIXA" - Felisberto, Alexandre; Marchiori, Fernanda; Gruber, Vilson (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article presents the use of PMBOK (Project Management Body of Knowledge) techniques in the CAIXA Representative Project in a Municipality with more than 100,000 inhabitants to obtain quantitative and qualitative indicators of financing operations, My House My Life (MCMV) and transfer of guides by CAIXA, in the capacity of Mandatory of the Union. For this purpose, the evolution of a portfolio with 18 contracts and investment value of 132.36 million Reais over six months, before and after the performance of CAIXA employee in the Representative Project CAIXA. This portfolio consists of housing projects, macro-drainage public works, paving, construction of gymnasiums, squares, among others. The works were spacious, with paralyzed works, with improvement after the implementation of the RC project.